Patient with suspected co-infection of hemorrhagic fever with renal syndrome and malaria: a case report - Zhao, Han-Dong; Qian, Hong-Bo; Wang, Ze-Kun; Ren, Rui-Kang; Yu, Tong-Bo; Liu, Hong-Li (Frontiers in Medicine, 2024)
Background Hemorrhagic fever with renal syndrome (HFRS) is a natural epidemic disease that can be caused by the Hantaan virus (HTNV). Malaria, the causative agent is plasmodium and can be transmitted by the mosquito bite. The similar manifestations shared by these disorders pose a challenge for clinicians in differential diagnosis, in particular, coupled with a false positive serological test.Case presentation A 46-year-old male was admitted for fever, and chill for over ten days, and was suspected to be co-infected with HFRS and Malaria for a history of travel to the endemic areas of Malaria coupled with a positive test of HTNV-Immunoglobulin M (IgM). Although leukocytosis, thrombocytopenia, renal injury, lymphocytosis, overexpression of interleukin-6, and procalcitonin were observed during the hospitalization, the hypotensive, oliguria, and polyuria phases of the HFRS course were not observed. Instead, typical symptoms of Malaria were found including a progressive decrease in erythrocytes and hemoglobin levels with signs of anemia. Furthermore, given that the patient without a history of exposure to the HFRS endemic areas, or exposure to the HTNV-infected rodent, nor the positive HTNV-IgG was observed, and the false serological test of IgM can be caused by various factors, the coinfection of HFRS with Malaria was ruled out.Misdiagnosis can be easily induced by the false serological test, in particular, the IgM test which can be influenced by various factors. A combination of health history, epidemiology, physical examination, precise application of specific examination involving the tests of conventional laboratory parameters as well as the well-accepted methods such as the Immunochromatographic (ICG) test, Real-time reverse transcription-polymerase chain reaction (PCR), and Western blot (WB), and well-acquainted of disorders with similar manifestations will contribute to the precise diagnosis in the clinical treatment.